The Impact of Scholarships on Students' Career Development: A Comparative Study in Higher Education Institutions - Salsabila Farahdiva; Steven Apriliardo; Regina Tira Julianti; Karyanti Karyanti; Asep Solikin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: Higher education plays a crucial role in improving the quality of human resources. However, not all students have equal access to resources, particularly in terms of educational financing. Scholarships serve as one solution to expand access, yet their impact on students' career development has not been widely examined. Aim: This study analyzes the relationship between scholarship status and students' career development. Method: The method employed is a quantitative, comparative design that compares scholarship recipients and non-recipients across career development categories. Results and Discussions: The results indicate that scholarship recipients tend to demonstrate better career development, with the majority falling into the "High" category. In contrast, students who do not receive scholarships are predominantly classified in the "Moderate" category. The discussion highlights that scholarships have a positive impact on career development by reducing financial burdens, thereby enabling students to focus more on competency development. Conclusion: Scholarship status has a significant influence on students' career development, and it is recommended that higher education institutions enhance scholarship programs integrated with career development initiatives.